Kosteneffizienz Deutscher Krankenhäuser im Bundeslandvergleich - Schmitz, Hendrik; Augurzky, B.

Objective work-nonwork conflict: From incompatible demands to decreased work role performance. - Haun, S; Steinmetz, Holger; Dormann, C (Journal of Vocational Behavior.)

A Need-Based Approach to Organizational Commitment and Job Involvement: Cross-Cultural Evidence from Germany and South Korea. - Steinmetz, Holger; Park, Y K; Kabst, Rüdiger (Journal of Managerial Psychology.)

A Typology of International New Ventures: Empirical Evidence from High Technology Industries. - Baum, M; Schwens, C; Kabst, Rüdiger (Journal of Small Business Management (JSBM).)

An Exploratory Cross-National Study of Information Sharing and Human Resource Information Systems. - Chae, B; Prince, J B; Katz, J; Kabst, Rüdiger (Journal of Global Information Management.)

Arbeitgebermarkenaufbau durch informelle Hochschul-Personalmarketingmaßnahmen: Eine empirische Analyse im deutschen Mittelstand. - Baum, M; Kabst, Rüdiger (Zeitschrift für Betriebswirtschaft (ZfB).)

Conceptual and Methodological Issues in Comparative HRM Research: The Cranet Project. - Steinmetz, Holger; Schwens, C; Wehner, M C; Kabst, Rüdiger (Human Resource Management Review (HRMR).)

Entry Learning, Age at Internationalization, and Foreign Venture Performance of Young Technology Firms. - Schwens, C; Kabst, Rüdiger (Schmalenbach Business Review (sbr).)

High involvement information sharing practices: An international perspective. - Prince, J B; Katz, J; Kabst, Rüdiger (International Journal of Human Resource Management.)

Human Resource Management and Early Internationalization: Is there a Leap-Frogging in International Staffing? - Isidor, R; Schwens, C; Kabst, Rüdiger (International Journal of Human Resource Management (IJHRM).)

International Entrepreneurship: A Meta-Analysis. - Schwens, C; Isidor, R; Bierwerth, M; Kabst, Rüdiger (Best Paper Proceedings of the 2011 Academy of Management.)

Internationalization of young technology firms: A complementary perspective on antecedents of foreign market familiarity. - Schwens, C; Kabst, Rüdiger (International Business Review (IBR).)

The Moderating Impact of Informal Institutional Distance and Formal Institutional Risk on SME Entry Mode Choice. - Schwens, C; Eiche, J; Kabst, Rüdiger (Journal of Management Studies (JMS).)

Three Approaches to Estimate Latent Interaction Effects: Intention and Perceived Behavioral Control in the Theory of Planned Behavior. - Steinmetz, Holger; Davidov, E; Schmidt, P (Methodological Innovation)

Intelligent Decision Support for Centralized Coordination during Emergency Response - Wex, Felix; Schryen, Guido; Neumann, Dirk (Proceedings of the 8th International Conference on Information Systems for Crisis Response and Management (ISCRAM 2011))

A formal approach towards measuring trust in distributed systems - Schryen, Guido; Volkamer, Melanie; Ries, Sebastian (Proceedings of the 26th Annual ACM Symposium on Applied Computing)

Is open source security a myth? What do vulnerability and patch data say? - Schryen, Guido (Communications of the ACM (CACM))

Seeking the VALUE in IS Business Value Research - An Agenda for investigating Synergies Between Socio-organizational Change, IS Capabilities Change, and IS Innovation - Schryen, Guido (IS Capabilities Change, and IS Innovation, Proceedings of the 19th European Conference on Information Systems (ECIS 2011), Helsinki)

Self-Stabilizing DeBruijn Networks - Richa, Andrea W.; Scheideler, Christian (Proceedings of the 13th International Symposium on Stabilization, Safety, and Security of Distributed Systems (SSS))
This paper presents a dynamic overlay network based on the De Bruijn graph which we call Linearized De Bruijn (LDB) network. The LDB network has the advantage that it has a guaranteed constant node degree and that the routing between any two nodes takes at most O(log n) hops with high probability. Also, we show that there is a simple local-control algorithm that can recover the LDB network from any network topology that is weakly connected.

Editorial bwp@ 20 - Tramm, T.; Kremer, H.-Hugo; Tenberg, R. (bwp@ Ausgabe 20, Lernfeldansatz 15 Jahre danach)